THE LUPININE MOLECULE: A JOURNEY INTO ITS CRYSTALLOGRAPHIC STRUCTURE (Scientific journal of the Fergana State University, 2024)
This research paper aims to investigate the structure, properties, and potential applications of lupinine, a bicyclic alkaloid found in various plant species. The study utilizes crystallographic analysis, including X-ray diffraction and Hirshfeld surface analysis, to gain insights into the molecular structure, intermolecular interactions, and physical properties of lupinine. The research highlights the originality of the study and presents findings regarding the biological activities, pharmacological potential, and agricultural applications of lupinine. The results contribute to the understanding of lupinine's structure-function relationship and its potential as a source for the development of new drugs and eco-friendly pesticides.